2012
DOI: 10.1016/j.tim.2012.08.009
|View full text |Cite
|
Sign up to set email alerts
|

New-found fundamentals of bacterial persistence

Abstract: Persister cells display tolerance to high doses of bactericidal antibiotics and typically comprise a small fraction of a bacterial population. Recently, evidence was provided for a causal link between therapy failure and the presence of persister cells in chronic infections, underscoring the need for research on bacterial persistence. A series of recent breakthroughs have shed light on the multiplicity of persister genes, the contribution of gene expression noise to persister formation, the importance of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
121
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(128 citation statements)
references
References 81 publications
4
121
3
Order By: Relevance
“…4C). Then, when the population meets environmental triggers inducing stringent or SOS responses, the basal level of expression increases, leading to an increase in the percentage of cells reaching the threshold (94,159). This hypothesis has been supported by experiments performed with TA modules that also demonstrate that the amount by which the threshold is exceeded determines the duration of dormancy (160).…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 81%
See 3 more Smart Citations
“…4C). Then, when the population meets environmental triggers inducing stringent or SOS responses, the basal level of expression increases, leading to an increase in the percentage of cells reaching the threshold (94,159). This hypothesis has been supported by experiments performed with TA modules that also demonstrate that the amount by which the threshold is exceeded determines the duration of dormancy (160).…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 81%
“…Even when enrichment is significant, it is important that not all dormant bacteria are persisters; conversely, all persisters do not necessarily correspond to dormant cells (93). Therefore, it is likely that passive dormancy per se is not entirely responsible for the persister phenotype (94). A recent study confirmed these findings by using flow cytometry sorting of E. coli cells based on their level of metabolic activity and/or cell division (95).…”
Section: Persisters Play a Central Role In Biofilm Recalcitrance Towamentioning
confidence: 94%
See 2 more Smart Citations
“…Persister cells are formed through random intrinsic fluctuations of protein levels, such as the well-studied stable toxins expressed by chromosomal toxin-antitoxin (TA) modules (10)(11)(12)(13). Spontaneous gene expression and noise during transcription and translation, amplified by feedback regulatory processes, also give rise to fluctuating protein levels of persister genes that result in a dormant multidrug-tolerant state (3,14). Since the formation of persister cells is a result of a variety of mechanisms, the subpopulation of persisters is heterogenous.…”
mentioning
confidence: 99%